THE ACCOUNTING EXCHANGE. - Coleman, L. W. (The Accounting Review, 1943)
Mastery of bookkeeping is fundamentally a development of the ability to decide which accounts should be debited and credited in the recording of transactions. Analysis of this type must precede recording. Since this concept is fundamental to all bookkeeping and accounting, it is important that it be introduced early in every bookkeeping course in such a manner that it will be thoroughly mastered. The difference between a $20-a-week book keeper and the much higher salaried auditor is largely in the ability to analyze accounting data. The most common weakness of students from high-school book- keeping classes that enroll in beginning accounting course is their lack of ability to analyze. Their handicap seems to be that though they know something of the "how" of bookkeeping, they do not seem to understand the "why" and thus lack ability to do accounting, for they are not able to deal with new or unusual situations. They need more definite, purposeful training in transaction analysis.